2023
DOI: 10.1002/cbic.202200798
|View full text |Cite
|
Sign up to set email alerts
|

ROS‐Triggered Gel‐Sol Transition and Kinetics‐Controlled Cargo Release by Methionine‐Containing Peptides

Abstract: The gel-sol transition of self-assembling peptides is a useful switch for environment-dependent drug release. For their applications, kinetics control of the responses is important for matching the velocity of release to the target biological events.Here we demonstrate the chemical control of redox-triggered gel-sol transition kinetics of self-assembling peptides by altering the amino acid sequence. Amphiphilic peptides were developed in which a methionine residue was located in the middle (JigSAP-IMI) or near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Oscillatory rheology measurements of the three peptide materials showed higher storage moduli ( G ′) than loss moduli ( G ″) (Figure S2 and Table S1), and the rheological properties were essentially unchanged depending on frequency (Figure S3), indicating hydrogel formation. Analogous to JigSAP-MII reported previously, transmission electron microscopy (TEM) observations confirmed that JigSAP-MIM had formed nanofibers (Figure a). The circular dichroism (CD) spectrum of the JigSAP-MIM hydrogel showed a characteristic negative Cotton effect at 218 nm (Figure b­(solid line)), and the infrared (IR) spectrum exhibited a sharp vibrational band at 1620 cm –1 (Figure c­(solid line)).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oscillatory rheology measurements of the three peptide materials showed higher storage moduli ( G ′) than loss moduli ( G ″) (Figure S2 and Table S1), and the rheological properties were essentially unchanged depending on frequency (Figure S3), indicating hydrogel formation. Analogous to JigSAP-MII reported previously, transmission electron microscopy (TEM) observations confirmed that JigSAP-MIM had formed nanofibers (Figure a). The circular dichroism (CD) spectrum of the JigSAP-MIM hydrogel showed a characteristic negative Cotton effect at 218 nm (Figure b­(solid line)), and the infrared (IR) spectrum exhibited a sharp vibrational band at 1620 cm –1 (Figure c­(solid line)).…”
Section: Resultsmentioning
confidence: 99%
“…Proteins that function in environments where ROS can be overproduced possess multiple Met residues in their surface-exposed domains to allow the effective scavenging of ROS . The redox reactivity of Met has inspired the design of biomaterials responsive to ROS. Redox-responsive polypeptides based on Met have been designed to control properties such as the thermal phase transition upon oxidation . In addition, self-assembling peptides have been recognized as highly important components for designing biomaterials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-assembling peptides are another class of biomaterials for developing ECMmimetics with several important advantages, such as the possibility of tailoring the properties by modifying the amino acid sequences, the capability to form three-dimensional networks affording hydrogels, and high biocompatibility. [12][13][14][15][16][17][18][19][20][21][22][23] By incorporating bioactive motifs such as RGD, the functionalities of the selfassembling peptides can be tuned and expanded to show cell adhesive properties. [24][25][26] For functionalizing the membranes with transportation capabilities, synthetic membrane channels have been extensively developed.…”
Section: Takahiro Muraokamentioning
confidence: 99%
“…In addition, peptide fibres that exhibit various dynamic behaviours can be designed by tuning the amino acid sequences, particularly in the hydrophobic part. [20][21][22][23] For example, it has been reported that the conformational flexibility of peptide fibres can be a critical factor in controlling the stiffness of the hydrogels made of the entangled supramolecular nanofibres. Introducing glycine residues generally enhances the conformational flexibility of polypeptide chains.…”
Section: Feature Article Chemcommmentioning
confidence: 99%